1996
DOI: 10.1002/(sici)1096-9071(199601)48:1<8::aid-jmv2>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hepatitis B virus genotypes and pre-core region variability during interferon treatment of HBe antigen negative chronic hepatitis B

Abstract: The clinical importance of hepatitis B virus (HBV) genome variability has been reported recently. One example is the occurrence of hepatitis B virus pre-core mutants, which arise during spontaneous or interferon-induced seroconversion from HBeAg to anti-HBe and are thought to be selected by immune pressure. A survey of HBV pre-core mutants and viral genotypes in 35 HBeAg negative patients during interferon therapy was carried out to understand viral pathogenesis in this form of chronic hepatitis B. Seventeen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(28 citation statements)
references
References 26 publications
0
26
0
2
Order By: Relevance
“…However, three patients have not exhibited HBeAg seroconversion following initial therapy; these three patients subsequently underwent other treatments, but all have remained HBeAg ϩ . It has been reported that the response to INF therapy is excellent in patients with HBV genotype A chronic hepatitis compared to those with the HBV genotype D. [19][20][21] We speculate that resistance of HBeAg to seroconversion in Japanese patients characterizes the HBV genotype A, in virological terms, once the initial opportunity to treat this disease is missed.…”
Section: Discussionmentioning
confidence: 86%
“…However, three patients have not exhibited HBeAg seroconversion following initial therapy; these three patients subsequently underwent other treatments, but all have remained HBeAg ϩ . It has been reported that the response to INF therapy is excellent in patients with HBV genotype A chronic hepatitis compared to those with the HBV genotype D. [19][20][21] We speculate that resistance of HBeAg to seroconversion in Japanese patients characterizes the HBV genotype A, in virological terms, once the initial opportunity to treat this disease is missed.…”
Section: Discussionmentioning
confidence: 86%
“…Genotype A, in contrast, is not common in Japan, and was not common even in the early years of HBV studies, 1,2 the G-to -A 1896 mutation in the precore region rarely occurs, and interferon therapy results in a marked response. 16,17 Because the therapeutic response of patients with genotype A is different from that in patients with genotype C who are positive for HBeAg, further studies are necessary to clarify the virological characteristics and therapeutic responses of Japanese patients with genotype A HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a study from India, where HBV genotypes A and D are dominant, noted that genotype D was associated with more severe liver disease and a higher incidence of HCC than genotype A [10]. HBV genotype was also related to the responses to antiviral therapies, including interferon and lamivudine treatments [11][12][13][14][15][16]. A relationship between HBV genotypes and mutations in the pre-core and core promoter regions that may diminish the HBeAg production has been documented [8,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 95%